Pedagogical impact of integration of musculoskeletal anatomy blended learning on physiotherapy education - Delafontaine, Arnaud; Saiydoun, Gabriel; Frigout, Jérôme; Fabeck, Laurent; Degrenne, Olivier; Sarhan, François-Régis (Frontiers in Medicine, 2023)
Background: In physiotherapy education, blended learning is recognised to be more effective compared to traditional teaching. The aim of this study was to assess the consequences of a musculoskeletal anatomy blended learning program on skills developed by students. Methods:We conducted an observational retrospective monocentric study in a French physiotherapy school named "X". Ninety-two first-year students in the 2017-18 baseline group (students with traditional face-to-face learning), and ninety-eight first-year students and ninety-five secondyear students in the 2018-19 and 2019-20 blended learning experimental groups was included.A success rate of the anatomy final written exam, defined by the percentage of students scoring 50% or above, was analysed between 2017 and 2020. We also evaluated the pedagogical value of musculoskeletal e-learning and its usefulness for preparing the student for their anatomy final written exam at «X». Results: We observed an improvement in the success rate of the anatomy final written exam between the 2017-18 baseline group, 2018-19 and 2019-2020 experimental groups during first (Kruskal-Wallis = 74.06, df = 2, p<.001) and second semester (Kruskal-Wallis = 173.6, df = 2, p<.001) We obtained a data survey and questionnaire response rate of 74% (n = 89/120) for the 2018-19 and 62% (n = 72/116) for the 2019-20 experimental groups. Concerning questionnaire response, they were no significant statistical difference between 2018-19 and 2019-20 experimental groups. Conclusions: Blended learning could improve student success rate of the anatomy final written exam and learning of professional physiotherapy skills.